Inequality of Outcomes vs. Inequality of Opportunities in a Developing Country. An exploratory analysis for Chile - Nuñez, Javier (Estudios de Economía, 2016)
We apply a variation of Bourguignon, Meléndez and Ferreira (2005) methodologyto examine the extent to which income inequality is associated with the inequalityof observed exogenous circumstances of origin that determine individuals’“opportunities” to pursue their chosen life plans. We find that equalizing a set ofobserved circumstances of origin across individuals such as parents’ schooling,parents’s stability of employment, father’s age, household size and growing ina single vs a bi-parental household reduces income inequality, but in a smallmargin, in the range of 8 to 13 points of the Gini coefficient, about a 15-20 percent drop. These results are similar to those obtained by Bourguignon et al.(2005) for Brazil, although the dataset and the set of observed circumstancesare partially different. These results suggest that a significant part of incomeinequality may be associated with unobserved heterogeneity across individualsunrelated to circumstances of origin, such as preferences, effort and sheer luck,transitory shocks and measurement errors in income. However, assessing therelative importance of these factors vs. the role of unobserved circumstancesremains as future research.